PERSEPSI SISWA SEBAGAI PEMILIH PEMULA TERHADAP PEMILU PRESIDEN DI SMA NEGERI SEKECAMATAN ILIR BARAT I KOTA PALEMBANG - Dina Permata Jannah; Alfiandra Alfiandra; Emil El Faisal (Bhineka Tunggal Ika: Kajian Teori dan Praktik Pendidikan PKn, 2014)
This research title â€student perception as the beginner voters to the election of president at 2014 in senior high schoolâ€ in sub district ilir barat I palembang city. Destination of this research is knowing how is student peceptiont as the beginner voters to the election of president at 2014 in senior high schoolâ€ in sub district ilir barat I palembang city. This research is a research with population is tudent class XII wich is at 17th age in senior high schoolâ€ in sub district ilir barat I with population 493 student as the beginner voters wiich is to be a sample than until 10-15% of the population because subject of the reseach more than 100, so with the reseach use stratified randonm sampling tehnic.Â  stratified randonm sampling tehnic is taken sample by stratified. The sampe in this research 50 population taken from class XII in 17th age. The colectionÂ  documentation technic by photograph and questioner from the analisis and the discussion of dokumentation inferred that positive categoriez was show average value 152,7 with 66,95% percentage.